Estimating habit-forming and variety-seeking behavior: Valuation of recreational birdwatching - Guilfoos, Todd; Kolstoe, Sonja; Thomas, Priya (American Journal of Agricultural Economics, 2024)
Past experiences influence choices, and people's preferences for more similar (habit-forming) or different (variety-seeking) experiences are reflected in these choices. We develop a structural estimation framework to capture whether people are habit forming or variety seeking and apply it to the choice of recreation site. This research contributes to the revealed preference literature by demonstrating how to account for habit or variety-seeking behavior in recreation site choice models in a two-stage framework. Using this framework, we estimate similarity weights that reflect the birders habit formation and variety seeking preferences. Predicted probabilities from the first stage model are then incorporated into the second stage, a mixed logit recreation site choice model of bird watching trips from eBird, by their members. We find that including the dynamic elements of choice, specifically variety-seeking behavior, can double the estimated willingness to pay (WTP) for individual sites relative to the static model. Although our sample of bird watching trips taken by eBird members is a sample of convenience, these results suggest that static models of recreation site choice are a lower bound on our recreation demand WTP estimates. We find variety-seeking preferences are related to land cover and the site's fixed attributes, whereas habit formation appears for seasonality in the bird watching context.
Keywords: Citizen Science; Habit Formation; Site Choice; Variety Seeking; Case-Based Reasoning